2022
DOI: 10.1007/s00068-022-02055-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 3D printing on inter- and intrarater reliability on the classification of tibial plateau fractures

Abstract: Purpose Tibial plateau fractures continue to be a challenging task in clinical practice and current outcomes seem to provide the potential for further improvement. Especially presurgical understanding of the orientation of fracture lines and fracture severity is an essential key to sufficient surgical treatment. The object of this study was to evaluate the reliability of modern axial CT-based classification systems for tibial plateau fractures. In addition, the diagnostic-added value of 3D printi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Through all of this, the use of 3D printing technology is becoming more evident. This study and others suggest that fracture assessment using 3D-printed patient-speci c models is superior, aids in the preoperative planning process, and may ultimately improve patient outcomes 23,25,27,30 . However, the use of these specimens should always be combined with a thorough study of the CT scans, 3D volumetric reconstructions, and other conventional imaging techniques that should form the basis of any fracture evaluation 31 .…”
Section: Discussionmentioning
confidence: 66%
“…Through all of this, the use of 3D printing technology is becoming more evident. This study and others suggest that fracture assessment using 3D-printed patient-speci c models is superior, aids in the preoperative planning process, and may ultimately improve patient outcomes 23,25,27,30 . However, the use of these specimens should always be combined with a thorough study of the CT scans, 3D volumetric reconstructions, and other conventional imaging techniques that should form the basis of any fracture evaluation 31 .…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the implementation of point-of-care 3D printing may add value to the use of conventional imaging modalities alone. In particular, Dust et al showed that the 3D printing group had higher interobserver reliability than CT and 3D CT alone in clinically less experienced readers [ 14 ]. However, it does requires time management and planning to implement this technology into daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Technical advances have considerably improved medical treatment practices, and 3D printing (3DP) techniques have been applied to the field of orthopedics [7][8][9][10][11][12]. Recently, several studies have shown that 3DP, the rapid prototyping technology, can be used for efficient preoperative plate contouring as per the exact surface of the individualized 3DP bone model [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%